2007
DOI: 10.1002/jcp.21016
|View full text |Cite
|
Sign up to set email alerts
|

Osterix is a key target for mechanical signals in human thoracic ligament flavum cells

Abstract: Mechanical stress is considered to be an important factor in the progression of thoracic ossification of the ligament flavum (TOLF). To elucidate the mechanism underlying mechanical stress-induced TOLF, we investigated the effect of stretching on cultured flavum ligament cells derived from TOLF and non-TOLF patients. We found that the mRNA expression of alkaline phosphatase (ALP), osteocalcin, Runx2, and osterix, but not that of Dlx5 and Msx2, was significantly increased by stretching in TOLF cells. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
0
40
1
Order By: Relevance
“…OPN reactivity in the cement line and surface of cementum and alveolar bone might be induced by osterix expression. Their strong localization in periodontal tissues when 100 g of heavy force was applied indicates that they might be molecules linking mechanostressing and osteogenic and odontogenic differentiation 20,23,24 and might be involved in bone, PDL, and cementum remodeling during orthodontic tooth movement. The precise relationship between OPN and osterix during periodontal tissue remodeling in response to heavy force could not be ascertained with the current methodology.…”
Section: Discussionmentioning
confidence: 99%
“…OPN reactivity in the cement line and surface of cementum and alveolar bone might be induced by osterix expression. Their strong localization in periodontal tissues when 100 g of heavy force was applied indicates that they might be molecules linking mechanostressing and osteogenic and odontogenic differentiation 20,23,24 and might be involved in bone, PDL, and cementum remodeling during orthodontic tooth movement. The precise relationship between OPN and osterix during periodontal tissue remodeling in response to heavy force could not be ascertained with the current methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the activation of MAPK signaling cascade contributes to osteogenic differentiation of cultured LFCs induced by mechanical stress and leptin, which were considered as the causes of OLF [25,43]. However, whether the activation of ERK1/2 and p38 MAPK is involved in rhGDF-5 induced LFCs differentiation need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, activation of p38 MAPK by BMP-2 has been shown to be relevant in the osteogenic effects of this cytokine (38 -40). Furthermore, the inhibition of the p38 pathway strongly inhibits Osx expression induced by BMP-2, insulinlike growth factor-I, or mechanical stress (41)(42)(43). Thus, we analyzed whether Dlx5 could be a target of the p38 pathway.…”
Section: Volume 283 • Number 7 • February 15 2008mentioning
confidence: 99%